PENGEMBANGAN ALAT PERAGA BAHAYA ROKOK DAN MEKANISME PERNAPASAN PADA PEMBELAJARAN IPA TERPADU DI SMP - Annisa Fikriya; Dinar Maftukh Fajar (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2020)
Science learning using conventional methods and the unavailability of learning media can make learning atmosphere less enjoyable. Therefore, we need learning media that can make learning more fun. In addition, we need media that can demonstrate the phenomenon of natural and environmental damage and can socialize the dangers of smoking to students. This is because the danger of smoking is relevant to one of the natural science materials in junior high school, namely the respiratory system. This research aimed to develop props about the dangers of smoking and the respiratory system in learning science in junior high school. This type of research is classified as Research and Development with the ADDIE model developed by Robert Maribe Branch. The data collection instruments used were questionnaires given to media experts to examine the validity of the props and questionnaires given to students to gain their responses about the props. The product developed has been tested by media experts and received a percentage score of 88.4% which belongs to the